PENGARUH STRENGHT BASED PARENTING TERHADAP KESEJAHTERAAN SUBJEKTIF SISWA - Zuhri, Mohammad Syarifudin; Aulia, Lailatuzzahro Al-Akhda (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to empirically examine the effect of strength-based parenting on students’ subjective well-being. The background of this research is grounded in the importance of parental roles in providing parenting that not only emphasizes behavioral control but also focuses on the development of children’s potentials, strengths, and abilities. The research method employed was quantitative with a correlational approach to determine the direction and magnitude of the relationship between variables. The instruments used consisted of a strength-based parenting scale and a student subjective well-being scale, both of which had undergone validity and reliability testing. The collected data were analyzed through classical assumption tests, including normality and linearity, followed by simple regression analysis. The results revealed a significant positive relationship between strength-based parenting and students’ subjective well-being. These findings affirm that the higher the implementation of strength-based parenting by parents, the higher the level of students’ subjective well-being, both in emotional aspects and in academic development.